Hubungan Kepatuhan Transfusi Darah dan Kelasi Besi dengan Kualitas Hidup Anak Thalasemia - Armina Armina; Dwi Kartika Pebriyanti (Universitas Baiturrahim, 2021)
Children with Thalassemia rely heavily on therapy for the sake of continuity in living life. Specifically, the purpose of this study is: (1) knowing the picture of transfusion compliance and iron class in thalasemia, (2) knowing the picture of the quality of life of thalassemia children, (3) analyzing the relationship of transfusion compliance and iron class with the quality of life of thalasemia children. This research plan will use Crossectional study design. The location of this research will be conducted in hospitals in Jambi. The population of this study is children with Thalasemia using purposive sampling techniques with sample characteristics, namely thalasemia children aged 2-18 years who are treated at. Transfusion and iron grade compliance were measured by questionnaires. Quality of life was measured using a Quality of Life questionnaire based on pediatric PedsQL indicators. Data analysis will be done by Corelation Spearman test. The results showed that there is a relationship between compliance of blood transfusion and iron class with the quality of life of children thalasemia aspects of social function with a value of p 0.000, aspects of emotional function with p value of 0.021 and school function p value of 0.030